Dual‐Functional Coating of Forward Osmosis Membranes for Hydrophilization and Antimicrobial Resistance. Issue 12 (7th March 2016) - Liu, Qing; Li, Jingguo; Zhou, Zhengzhong; Qiu, Guanglei; Xie, Jianping; Lee, Jim Yang
Abstract : Microbial fouling and internal concentration polarization (ICP) are factors limiting the performance of forward osmosis (FO) membranes. These limitations in flat sheet thin film composite (TFC) FO membranes are mitigated by a single Ag/AgCl nanocomposite coating in this study. The coating is prepared by first adsorbing Ag + on the negatively charged carboxylate groups of polyacrylic acid (PAA)‐polyethersulfone (PES) blend membrane substrate (support layer). Cl − ions are introduced next to form a conformal AgCl coating in situ. Irradiation of the coating with visible light then converts it into a composite coating with nano‐Ag(n‐Ag) on the membrane substrate exterior and AgCl in the membrane substrate interior. The Ag/AgCl‐coated membranes prepared as such deliver good antimicrobial resistance concurrently with a high water flux. The antimicrobial performance can be attributed to a high loading of n‐Ag on the membrane exterior while the high water flux to the AgCl hydrophilization of the membrane interior which reduces the ICP. To the best of our knowledge, this is probably the first demonstration of a dual‐functional coating for FO TFC membranes. Abstract : An Ag/AgCl coating is applied to a thin film composite forward osmosis membrane by combining an alternative soaking process with visible light photolysis. The resulting high loading of nano‐Ag on the membrane exterior and the AgCl hydrophilization of the membrane interior give rise to a membrane with strong antibacterial resistance and high water flux.